2021
DOI: 10.13057/biodiv/d221129
|View full text |Cite
|
Sign up to set email alerts
|

presence of whale sharks based on oceanographic variations in Cenderawasih Bay National Park, Papua, Indonesia

Abstract: Abstract. Manuhutu JF, Wiadnya DGR, Sambah AB, Herawati EY. 2021. The presence of whale sharks based on oceanographic variations in Cenderawasih Bay National Park, Papua, Indonesia. Biodiversitas 22: 4948-4955. Oceanographic factors have an important role in the study of estimating the distribution of fish resource habitats. Sea Surface Temperature (SST), Sea Surface Chlorophyll (SSC), Current Speed, Sea Surface Height (SSH), and bathymetry are important parameters that have been used in estimating the habitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 40 publications
(60 reference statements)
0
0
0
Order By: Relevance
“…The result of Pearson analysis showed that there is a negative, very low correlation between the yearly average of whale shark appearance and yearly average chlorophyll-a concentration (r=0,029) (Figure 8), while there is a positive, low correlation between yearly average whale shark appearance and yearly average SST (r=0,279) (Figure 9). These findings are contrary to the study of Manuhutu et al (2021) which used the Generalized Additive Model (GAM) analysis of the presence of whale sharks in the waters of Cenderawasih Bay National Park, Papua, Indonesia, the oceanographic parameters that have the most influence are Sea Surface Temperature (SST) and Chlorophyll-a and indicated that there are several other oceanographic factors influenced the whale shark's appearance in Botubarani waters, such as Sea Surface Height Distribution (SSHD) and depth (Bathymetry). Since the oceanographic conditions in Indonesia are diverse and complex, further study is important to draw a firm conclusion.…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…The result of Pearson analysis showed that there is a negative, very low correlation between the yearly average of whale shark appearance and yearly average chlorophyll-a concentration (r=0,029) (Figure 8), while there is a positive, low correlation between yearly average whale shark appearance and yearly average SST (r=0,279) (Figure 9). These findings are contrary to the study of Manuhutu et al (2021) which used the Generalized Additive Model (GAM) analysis of the presence of whale sharks in the waters of Cenderawasih Bay National Park, Papua, Indonesia, the oceanographic parameters that have the most influence are Sea Surface Temperature (SST) and Chlorophyll-a and indicated that there are several other oceanographic factors influenced the whale shark's appearance in Botubarani waters, such as Sea Surface Height Distribution (SSHD) and depth (Bathymetry). Since the oceanographic conditions in Indonesia are diverse and complex, further study is important to draw a firm conclusion.…”
Section: Resultscontrasting
confidence: 99%
“…Meanwhile, juvenile whale sharks tend to be found congregating in shallow waters near the coast (Dove and Pierce, 2021). In Indonesia, the whale shark is also found in Cenderawasih Bay, Papua (Manuhutu et al, 2021), Talisayan waters, Kalimantan (Himawan et al, 2017), and Probolinggo waters (Syah et al, 2018;Kapinangasih et al, 2022). Large adult whale sharks are rarely found on the coasts because of their diving abilities and adaptations that allow them to obtain more prey in deep waters (Dove and Pierce, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, in Cenderawasih Bay National Park, SST and SSC parameters are the two most critical characteristics influencing the presence of whale sharks, followed by SSHD, depth (bathymetry), and current parameters. On the other hand, human activities affecting fish and their habitats, such as fishing and tourism, are accountable for declining whale shark populations (Anna and Saputra 2017;Manuhutu et al 2021). A previous study conducted by Md-Zain et al (2018a) demonstrated that 88.2% of individuals were found in a local market in Malaysian Borneo where sharks were endangered (Lamiopsis tephrodes, Sphyrna mokarran, and Sphyrna lewini), vulnerable (Alopias pelagicus and Rhynchobatus australiae), and near threatened (Carcharhinus limbatus, griseum, Carcharhinus sorrah, and Carcharhin).…”
Section: Discussionmentioning
confidence: 99%
“…A horizontal line at zero indicates no parameter effect. GAM function modeling above the zero axis indicated a strong (positive) influence of a parameter and vice versa [25].…”
Section: Catch Per Unit Effort (Cpue)mentioning
confidence: 99%